The Implants No Woman Wants: A Multimodality Review of Endometriosis - Cain , N.; Bahrami , S.; Masamed , R.; Dave , H.; Patel , M. (Seram, 2021)
Background Information: Endometriosis is one of the most common benign gynecological conditions in the pre-menopausal female population. Recent data suggest that 6.6% to 16.2% of reproductive-aged women in the United States are affected, with a peak incidence between 24 and 29 years of age. There is significant morbidity associated with endometriosis, including infertility and chronic pain. This constitutes concern in both public health and women’s health. Understanding the pathophysiology and imaging features on multiple modalities is essential for the radiologist. Educational Goals/Teaching Points: On completion of this case-based review, the radiologist will be familiar with the pathophysiology, epidemiology and clinical presentation of endometriosis. He or she should recognize the different forms of endometriosis, the diagnostic dilemmas and common mimickers. In addition, the radiologist will appreciate the updated guidelines on management of endometriosis, including the different conservative and surgical approaches. Key Anatomic/Physiologic Issues and Imaging Findings/Techniques: This presentation will review a multimodality imaging approach of the three manifestations of endometriosis in the pelvis, including ovarian endometriomas, superficial peritoneal implants and deeply infiltrating endometriosis (DIE), as well as its presentation in other less common anatomic locations. The most recognized concepts of pathophysiology of the disease will be reviewed, which are retrograde menstruation, coelomic metaplasia, immune system abnormalities, genetic mechanisms and environmental and lifestyle factors. Common disease mimickers and potentials for misinterpretation will be discussed, with emphasis on key imaging findings and techniques for appropriate differentiation. Of importance, misclassification of endometrioma as ovarian borderline or malignant tumor can cause unnecessary anxiety and overtreatment for the patient. The most current treatment and management guidelines of the American Congress of Obstetricians and Gynecologists (ACOG) will be discussed as well as the revised American Society for Reproductive Medicine (r-ASRM) Classification System for staging endometriosis. Conclusion: Accurate recognition of endometriosis is significant to women’s reproductive health and general psychological and physical well being. The radiologist plays a critical role in the healthcare team setting to reach a diagnosis and provide proper treatment tailored to each individual and extent of their disease.